2020
DOI: 10.1063/5.0005808
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of monoclinic- and orthorhombic-based (BxGa1−x)2O3 alloys

Abstract: Gallium oxide has been attracting much interest due to its tremendous potential for power device application. The (BxGa1−x)2O3 ternary alloys of monoclinic and orthorhombic phases with the B-content covering the full composition were studied using first-principles density functional theory calculations. The effect of the B-content on the structural and electronic properties of (BxGa1−x)2O3 alloys is discussed. The formation enthalpy of the ternary alloys has been investigated, indicating the feasibility of syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 66 publications
0
11
0
Order By: Relevance
“…Wide band-gap (WBG) materials, such as gallium nitride (GaN) and silicon carbide (SiC) [3], are those which can satisfy the application's requirements [4,5]. SiC and GaNbased devices are being more and more employed in converters for the automotive environment [6][7][8][9][10][11][12][13][14][15][16][17][18][19] thanks to their superior electrical and thermal performances in comparison to that of silicon (Si). SiC devices are more indicated for high-voltage and high-power, while GaN-based ones are more prone to low-and medium-power high-frequency applications with low and medium voltages.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wide band-gap (WBG) materials, such as gallium nitride (GaN) and silicon carbide (SiC) [3], are those which can satisfy the application's requirements [4,5]. SiC and GaNbased devices are being more and more employed in converters for the automotive environment [6][7][8][9][10][11][12][13][14][15][16][17][18][19] thanks to their superior electrical and thermal performances in comparison to that of silicon (Si). SiC devices are more indicated for high-voltage and high-power, while GaN-based ones are more prone to low-and medium-power high-frequency applications with low and medium voltages.…”
Section: Introductionmentioning
confidence: 99%
“…Some possible GaN structures are reported in [7]. Nowadays, ultra-wide-bandgap materials such as gallium oxide (Ga 2 O 3 ) [8][9][10], diamond, and aluminium nitride (AlN), have also been gaining attention in the power electronics field, even if at a more infant stage. A review of Ga 2 O 3 -based power MOSFETs can be found in [11].…”
Section: Introductionmentioning
confidence: 99%
“…It plays an important role when experiments are difficult to conduct for heat transfer simulation. These laws are used for the theoretical computation of heat transfer [8][9][10]. The above discussed laws are used for evaluation of heat flux in two phase fluids as well as regular fluids.…”
Section: Introductionmentioning
confidence: 99%
“…is will help the alloys in reducing friction drag and enhancing the transfer of heat. ese types of characteristics of nanoparticles and the like are appropriate and applicable to all devices used for cooling or heating purposes [9][10][11][12][13]. Normal nanoparticles, i.e., gold, copper, aluminum, and titanium, and ferrite nanoparticles, i.e., nickel zinc ferrite, manganese zinc ferrite, and magnetite ferrite, were used by scientists and mathematicians in the history [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%